Experimental study on the influence of the nitrogen concentration in the oxidizer on NOx and CO emissions during the oxy-fuel combustion of natural gas. (1st January 2021) - Gaber, Christian; Schluckner, Christoph; Wachter, Philipp; Demuth, Martin; Hochenauer, Christoph
Abstract: In this research, the influence of the nitrogen concentration in the oxidizer, oxygen/fuel equivalence ratio and temperature of the combustion chamber on the combustion characteristics of a natural gas fired oxy-fuel jet burner was observed. The thermal input of the fuel was 600 kW and the nitrogen concentration in the oxidizer was varied between 0 and 15 vol.-%, wherein either the maximum combustion chamber temperature or the thermal output were held constant. It was observed that in case of a constant combustion temperature, even small volume fractions of nitrogen in the oxidizer resulted in non-negligible reductions in the thermal output. Furthermore, the experimental results showed that an increase in the nitrogen concentration from 0 to 15 vol.-% caused an approximately eight-fold increase in the NO x emissions and a considerable decrease in the CO emissions. The impact of the oxygen/fuel equivalence ratio on the NO x emissions was negligibly small up to a nitrogen concentration of 2 vol.-%. A reduction of the oxygen/fuel equivalence ratio to near stoichiometric levels resulted in NO x emission factors below 52 mg/kWh. The influence of the oxygen/fuel equivalence ratio on the NO x emissions was significantly more pronounced with an increasing amount of nitrogen present in the oxidizer. Highlights: The combustion characteristics of a gas fired oxy-fuel jet burner were examined. High-temperature combustion tests with a thermal input of 600 kW were performed. The contamination of pure oxygen with up to 15 vol.-% nitrogen was simulated. Determination of NOx and CO emissions as a function of the nitrogen concentration. The effect of the oxygen/fuel equivalence ratio on the emissions was determined.